Daughter of smoke & bone - Taylor, Laini (Taylor, Laini. Daughter of smoke & bone trilogy, 2020)
"Around the world, black handprints are appearing on doorways, scorched there by winged strangers who have crept through a slit in the sky. In a dark and dusty shop, a devil's supply of human teeth grown dangerously low. And in the tangled lanes of Prague, a young art student is about to be caught up in a brutal otherworldly war. Meet Karou. She fills her sketchbooks with monsters that may or may not be real; she's prone to disappearing on mysterious "errands"; she speaks many languages--not all of them human; and her bright blue hair actually grows out of her head that color. Who is she? That is the question that haunts her, and she's about to find out. When one of the strangers--beautiful, haunted Akiva--fixes his fire-colored eyes on her in an alley in Marrakesh, the result is blood and starlight, secrets unveiled, and a star-crossed love whose roots drink deep of a violent past. But will Karou live to regret learning the truth about herself?"--Amazon